Tuning of temporo‐occipital activity by frontal oscillations during virtual mirror exposure causes erroneous self‐recognition. (25th September 2015) - Serino, Andrea; Sforza, Anna Laura; Kanayama, Noriaki; van Elk, Michiel; Kaliuzhna, Mariia; Herbelin, Bruno; Blanke, Olaf; Foxe, John
Abstract Self‐face recognition, a hallmark of self‐awareness, depends on 'off‐line' stored information about one's face and 'on‐line' multisensory‐motor face‐related cues. The brain mechanisms of how on‐line sensory‐motor processes affect off‐line neural self‐face representations are unknown. This study used 3D virtual reality to create a 'virtual mirror' in which participants saw an avatar's face moving synchronously with their own face movements. Electroencephalographic (EEG) analysis during virtual mirror exposure revealed mu oscillations in sensory‐motor cortex signalling on‐line congruency between the avatar's and participants' movements. After such exposure and compatible with a change in their off‐line self‐face representation, participants were more prone to recognize the avatar's face as their own, and this was also reflected in the activation of face‐specific regions in the inferotemporal cortex. Further EEG analysis showed that the on‐line sensory‐motor effects during virtual mirror exposure caused these off‐line visual effects, revealing the brain mechanisms that maintain a coherent self‐representation, despite our continuously changing appearance.